Monograph of Himatanthus sucuuba, a plant of Amazonian folk medicine - F. Amaral, Ana Claudia; P. Ferreira, José Luiz; B. Pinheiro, Maria Lúcia; de A. Silva, Jefferson Rocha (Pharmacognosy Reviews)
The importance of the genus Himatanthus in popular medicine is supported by reports from different local communities in the Amazonian region. Himatanthus sucuuba (Spruce) Woodson is a plant of the Apocynaceae family, popularly known in the northern region of Brazil as sucuuba, sucuba or janaguba, among others common names. In Brazil, latex, infusions and decoctions of the bark and poultices are used in folk medicine for the treatment of gastritis, inflammations, anaemia, arthritis, verminosis and tumor. Phytochemical studies led to the isolation of triterpene esters with anti-inflammatory activity and iridoids with significant cytotoxic activity. Currently, popular consumption of this plant has been spread out in other regions, mainly for tumor treatment purposes. This work presents not only a review of botanical, phytochemical and pharmacological publishings but also new results of monographic information about the latex, leaves and bark of Himatanthus sucuuba.
Keywords: Apocynaceae; Himatanthus sucuuba; botanical aspects; pharmacology; chemical constituents; etnopharmacology